In this research, we study the reserve requirement policies implemented by the Central Bank of Russia and European Central Bank. First, we analyse the legal framework of central banking activity in Russia and Europe and we investigate the main rules and features of reserve requirements policies both in Russia and Europe. - Iureva, Lidiia (2018)
Dissertação de Mestrado em Economia apresentada à Faculdade de Economia